A latent variable approach to measuring bridging social capital and examining its association to older adults' cognitive health. (2nd November 2021) - Peng, Siyun; Roth, Adam R.; Perry, Brea L.
ABSTRACT: Access to cognitive stimulation through social interactions is a key mechanism used to explain the association between personal networks, cognitive health, and brain structure in older adults. However, little research has assessed how best to operationalize access to novel or diverse social stimuli using social network measures, many of which were designed to study information diffusion within large whole networks (e.g., structural holes and bridging social capital). Using data from 277 adults in the Social Networks and Alzheimer Disease (SNAD) study, we aimed to evaluate such measures for use in research on cognitive aging using personal social networks. We found a positive association between individual measures of structural holes and cognitive health, but not with brain structure. Further, we extracted a latent measure of bridging social capital using multiple individual measures (i.e., structural holes, network diversity, weak ties, and network size) and found it was significantly associated with cognitive health and brain structure, supporting the utility of this concept and related measures in the study of cognitive aging. Finally, individual measures may underestimate the effects of multidimensional bridging social capital on cognitive health and brain structure compared to a latent measure that combines them.